Studi instrumen ceilometer allweather 8339 dan data hasil pengukuran di Stasiun Meteorologi Minangkabau Padang (Study of the allweather 8339 ceilometer instrument and measurement data at the Minangkabau Meteorological Station, Padang ) - Serly Samarantika; - Asrizal; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2018)
The cloud height measurement has important role in aviation field. One of instruments that is used to measure the cloud height is ceilometer. The existence of ceilometer isn’t so common in daily life unlike other weather elements measuring device such as thermometer, barometer and so on. This cause lack of learning source and knowledge over the cloud parameters for students or observers. For this reason, the research about ceilometer instrument is important. The aim of this research is to describe the operation principle of ceilometer and to determine the data results interpretation of the instrument to give support for instrument’s future development. This research can be classified into the descriptive research category. The object of the research is Ceilometer Allweather 8339 in Minangkabau International Airport and its data results during 14 days. The data was analyzed using analysis descriptive technique. This was executed by collecting any kinds of information from field and literatures. Based on the data analysis can be stated two of research results. First, ceilometer works based on Lidar Principle and using NWS ASOS Sky Condition Algorithm as programming algorithm. The transmitter is InGaAs Laser diode and Avalanche Photo Diode is used as receiver. Second, the measurement result data from 1st July 2017 until 14 July 2017 shows variative pattern in height, sky condition and amount of layers every hours. For example the date that consist of the most low clouds is 7th July 2017 and cloud rarely formed on 3rd July 2017